Bibliometric Analysis: Trends in Innovative Government Research - Dini Adhania; Ismail Nurdin (Institut Pemerintahan Dalam Negeri, 2022)
This research presents the results of a bibliometric analysis of research trends related to innovative government from the Scopus database from 2018 to 2022. The literature study employed Publish or Perish by Harzing for citations in metric form, Microsoft Office for data frequency analysis, and Vosviewer for visualizing data. The results showed that the innovative research publications of the government have increased from 2018 to 2021, although there was a non-significant decrease in 2019. These occurred due to advances in information technology that accompany government administration, which have become a significant topic in research. Furthermore, between January and October 2022, there have been no publications regarding innovative government, but it is expected that more studies will be published in 2022. From the 25 types of documents found, 21 articles were the most widely published. The most popular keywords include innovation, collaboration, government support, and innovative work behavior. Keywords: Innovative Government; Bibliometric Analysis; Scopus; Research Trend Abstrak Penelitian ini menyajikan hasil analisis bibliometrik terhadap tren penelitian terkait innovative government dari database Scopus dalam rentang tahun 2018 – 2022. Penelitian ini menggunakan metode penelitian melalui Publish or Perish by Harzing terhadap kutipan dalam bentuk metrik, Microsoft Office untuk analisis frekuensi data dan Vosviewer untuk visualisasi data. Temuan: Berdasarkan hasil penelitian, publikasi penelitian innovative government sejak tahun 2018 mengalami kenaikan hingga tahun 2021 meskipun terjadi penurunan yang tidak signifikan pada tahun 2019. Hal ini terjadi karena kemajuan teknologi informasi yang membarengi penyelenggaraan pemerintah semakin menjadi perhatian dan diminati oleh peneliti. Hingga Oktober tahun 2022 belum ada ditemukan publikasi mengenai innovative government. Penulis meyakini ada penelitian mendatang yang akan dipublikasi pada tahun 2022. Dari 25 literatur innovative government yang ditemukan, jenis dokumen yang paling banyak dipublikasi adalah artikel berjumlah 21 artikel. Kata kunci yang paling populer antara lain innovation, collaboration, government support, dan innovative work behavior. Hal ini berarti yang paling menjadi perhatian dalam pembaruan dalam penyelenggaraan pemerintahan adalah inovasi, kolaboriasi, dukungan pemerintah dan perilaku kerja yang inovatif. Kata kunci: Innovative Government, Analisis Bibliometrik; Scopus; Tren Penelitian